Evaluasi dan Perbaikan Proses Bisnis Layanan Pengaduan Masyarakat pada Dinas Komunikasi dan Informatika Kabupaten Sidoarjo menggunakan Metode Business Process Improvement (BPI) - Jesy Thesalonica Mononimbar; Nanang Yudi Setiawan; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Based on the Sidoarjo Regent Regulation Number 22 of 2015 concerning the Community Complaint Service Center. To improve information services by the Sidoarjo Regency government, the Sidoarjo Regency Community Complaints Service Center (P3M) was formed. P3M is part of the operational activities of the Department of Communication and Information of Sidoarjo Regency. In running the business process, there are still some potential errors that can affect the performance of the business processes that lead to non-optimal. Time goes by several processes that exceed the Standard Operating Procedure (SOP) has been agreed, the results of the responses that were not clear were answered by whom, and the reporter is late knowing the results of the complaint response. Therefore it is necessary to analyze and evaluate current business processes to overcome problems. This study uses Failure Mode and Effect Analysis (FMEA) to perform problem analysis and evaluation of business processes and using Business Process Improvement (BPI) for the improvement of business processes. Current business processes (as-is) and recommendations (to-be) are modeled using Business Process Modeling and Notation (BPMN) and then performed a simulation. On the results of the time analysis simulation of the business process of as-is acceptance of public complaints and recommendations for the business process of receiving public complaints (to-be), the average time increase is up to 30.62%. So it can be concluded that business process recommendations are able to optimize business process performance